DESIGNING AND CLONING NA GENE OF INFLUENZA A/H5N1 VIRUS INTO pHW2000 VECTOR FOR PREPARATION OF A CANDIDATE VACCINE MASTERSEED STRAIN - Thu Hang, Nguyen Thi; Thu Hang, Hoang Thi; Chi, Nguyen Hung; Trang, Vu Huyen; Ha, Chu Hoang; Nam, Nguyen Trung (Vietnam Journal of Biotechnology, 2018)
The influenza A/H5N1 virus is an RNA virus belonging to the family of Orthomyxoviridae. The highly pathogenic influenza A/H5N1 virus exhibit the ability to cause high mortality in poultry and infect humans. Technology for vaccine seed strain production of influenza A virus using reverse genetics requires the creation of recombinant vectors carrying viral genomic segments. To create recombinant pHW2000 vectors containing the neuraminidase (NA) gene segment encoding an important surface antigen of influenza A virus, two N1 NA gene structures were designed based on the NA gene sequences of two subtypes of highly pathogenic influenza A/H5N1 clade (clade 1.1 and clade 2.3.2.1c) and then inserted into pHW2000 vector. These two clades of highly pathogenic avian influenza viruses that are still circulating in Vietnam, with antigen homology and genetic relationships to many strains of influenza A viruses, have been suggested to be used for producing vaccines against emerging avian influenza A/H5N1 virus. Each NA gene construct consists of 1453 nucleotides in which two ends of the gene are two non-coding regions (46 nucleotides and 57 nucleotides) containing primer binding site and cleavage site of BsaI. In the middle of each NA gene is one region of 1350 nucleotides encoding 449 amino acids, ensuring catalytic function and antigenicity of NA protein. Two NA segments corresponding to the two clades of influenza A viruses were successfully cloned into pHW2000 vectors for the generation of two recombinant vectors pHW2000-NA clade 1.1 and pHW2000-NA clade 2.3.2.1c. These recombinant vectors will be used for production of candidate avian influenza vaccine strains using reverse genetics technique.